Epidemiology and management of cysticercosis and Taenia solium taeniasis in Europe, systematic review 1990-2011. - Lorenzo Zammarchi; Marianne Strohmeyer; Filippo Bartalesi; Elisa Bruno; José Muñoz; Dora Buonfrate; Alessandra Nicoletti; Héctor Hugo García; Edoardo Pozio; Alessandro Bartoloni; COHEMI Project Study Group (PLoS ONE, 2013)
Background Cysticercosis is caused by the invasion of human or pig tissues by the metacestode larval stage of Taenia solium. In Europe, the disease was endemic in the past but the autochthonous natural life cycle of the parasite is currently completed very rarely. Recently, imported cases have increased in parallel to the increased number of migrations and international travels. The lack of specific surveillance systems for cysticercosis leads to underestimation of the epidemiological and clinical impacts. Objectives To review the available data on epidemiology and management of cysticercosis in Europe. Methods A review of literature on human cysticercosis and T. solium taeniasis in Europe published between 1990-2011 was conducted. Results Out of 846 cysticercosis cases described in the literature, 522 cases were autochthonous and 324 cases were imported. The majority (70.1%) of the autochthonous cases were diagnosed in Portugal from 1983 and 1994. Imported cases of which 242 (74.7%) diagnosed in migrants and 57 (17.6%) in European travellers, showed an increasing trend. Most of imported cases were acquired in Latin America (69.8% of migrants and 44.0% of travellers). The majority of imported cases were diagnosed in Spain (47.5%), France (16.7%) and Italy (8.3%). One third of neurosurgical procedures were performed because the suspected diagnosis was cerebral neoplasm. Sixty eight autochthonous and 5 imported T. solium taeniasis cases were reported. Conclusions Cysticercosis remains a challenge for European care providers, since they are often poorly aware of this infection and have little familiarity in managing this disease. Cysticercosis should be included among mandatory reportable diseases, in order to improve the accuracy of epidemiological information. European health care providers might benefit from a transfer of knowledge from colleagues working in endemic areas and the development of shared diagnostic and therapeutic processes would have impact on the quality of the European health systems.